Development of VB.Net Based Educational Psychology Learning Media Applications - Syahputra, Fahmy; Putri, Tansa Trisna Astono; Manurung, Ricardo; Nurrahma, Suci; Ginting, Ariyantika Br (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This article aims to develop a learning multimedia application specifically designed to support the learning process of educational psychology using the VB.Net programming language. With the increasing utilization of technology in education, the need for effective and interactive learning materials is becoming more urgent. This application comes with various features including learning material modules, interactive quizzes, and evaluation of learning outcomes that allow users to track their learning progress. In addition, the app is designed to be easily accessed and used by teachers and students, both in the classroom and in a self-study environment. The application development process includes many stages, from requirements analysis, system design, software development to testing and evaluation. The trial results show that this application has the potential to improve understanding of educational psychology concepts and provide a more dynamic learning experience. Through the use of this application, students can learn more deeply and repeatedly, thus significantly increasing their motivation and learning outcomes.